Division of labor, economic specialization and the evolution of social stratification - Joseph Henrich; Robert Boyd (Max Planck Institute of Economics, 2007)
This paper presents a simple mathematical model that shows how economic inequality between social groups can arise and be maintained even when the only adaptive learning processes driving cultural evolution increases individual's economic gains. The key assumption is that human populations are structured into groups, and that cultural learning is more likely to occur within groups than between groups. Then, if groups are sufficiently isolated and there are potential gains from specialization and exchange, stable stratification can sometimes result. This model predicts that stratification is favored, ceteris paribus, by (1) greater surplus production, (2) more equitable divisions of the surplus among specialists, (3) greater cultural isolation among subpopulations within a society, and (4) more weight given to economic success by cultural learners. We also analyze how competition among societies, both egalitarian societies and those with differing degrees of stratification, influences the long-run evolution of the institutional forms that support social stratification. In our discussion, we illustrate the model using two ethnographic cases, explore the relationships between our model and other existing approaches to social stratification within anthropology, and compare our model to the emergence of heritable divisions of labor in other species.
Keywords: 330; Sozialstruktur; Evolutionsökonomik; Arbeitsteilung; Funktionelle Einkommensverteilung; Soziale Isolation; Sozialer Wandel; Lernprozess; Theorie